Pride and Prejudice against Personal Identity - R. L. Kochnev (Омский научный вестник: Серия "Общество. История. Современность")
The study is devoted to a reconstruction of David Hume’s views on personal identity issues. The affect of pride is considered as a possible criterion. Potential ethical consequences of such a view on the nature of personality and conditions for its identity are analyzed.